The Impact of Immigration and Integration Policies On Immigrant-Native Labor Market Hierarchies - Martin Guzi; Martin Kahanec; Lucia Mýtna Kureková (Masaryk University, Faculty of Economics and Administration, 2022)
Across European Union (EU) labor markets, immigrant and native populations exhibit disparate labor market outcomes, signifying widespread labor market hierarchies. While significant resources have been invested in migration and integration policies, it remains unclear whether these contribute to or mitigate labor market hierarchies between natives and immigrants. Using a longitudinal model based on individual-level EU LFS and country-level DEMIG POLICY and POLMIG databases, we explore variation in changes of immigration and integration policies across Western EU member states to study how they are associated with labor market hierarchies in terms of unemployment and employment quality gaps between immigrant and native populations. Our findings imply that designing less restrictive policies may help mitigate immigrant-native labor market hierarchies by reducing existing labor market disadvantages of immigrants and making the most of their potential.
Keywords: J15; J18; J61; K37; 330; decomposition; immigrant-native gaps; labor market; DEMIG POLICY database; immigrant integration; hierarchies.